The Influence of Transformational Leadership, Organizational Culture on The Performance of Labor BPJS Through Good Corporate Governance - Rekson Silaban; Dedi Purwana; I Ketut R. SUdiardhita (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
This study aims to examine and determine BPJS employees' performance through organizational culture and transformational leadership with Good Corporate Governance (GCG) as the mediating variable. This study uses a sample of 75 respondents representing all BPJS Ketenagakerjaan branch offices in Indonesia. The data testing method used in this study is multiple regression analysis using SPSS 25 software. There were five hypotheses tested and two hypothesis testing in this study through intervening variables tested with single test calculations. The results of statistical tests from this study state that all the hypotheses proposed in this study can be accepted, either directly or indirectly (mediated).